SOCIAL AND SOCIETAL BARRIERS IN UTILIZATION OF MATERNAL HEALTH CARE SERVICES IN RURAL PUNJAB, PAKISTAN - Sarfraz, Mariyam; Tariq, Saira; Hamid, Saima; Iqbal, Nafeesa (Journal of Ayub Medical College Abbottabad, 2016)
Background: The health status of pregnant women depends largely on the quality of the antenatal and delivery services available to them. Maternal mortality remains a major public health problem with antenatal and delivery care utilization remaining low in Pakistan. This study explores the perspectives of rural community members about the antenatal and delivery care services’ utilization by the community. Methods: A qualitative study was undertaken in the rural community of District Attock. Focus Group Discussions (FGD) were conducted with husbands, married women of child-bearing age with young children and mothers-in-law. Data was analysed manually using content analysis techniques. Results: Majority of the respondents sought antenatal care (ANC) after 3-4 months. They further reported that home was the preferred place of delivery followed by the local ’˜rural health centre’. The preferred attendant for delivery was the local Dai (traditional birth attendant). Major limitations to accessing ANC and delivery services were lack of knowledge about ANC, long distance and high transport costs to health care facilities. People had strong beliefs on faith healers (Pirs) and insufficient knowledge about danger signs. Traditional and customary practice as taweez dhaga, saya, purdah, non-availability of health care providers, and lack of trust on young community midwives led to people favouring the home based package of services provided by traditional birth attendants (Dais). Conclusion: The findings of this study indicate that demand side barriers such as lack of knowledge regarding home based care, social barriers, financial constraint and non-acceptability of community midwives (CMW) because services offered by traditional birth attendants (TBA) were more accessible in terms of distance and cost are a major challenge affecting utilization. Efforts towards ensuring the utilization of ANC and delivery services should be targeted towards rural areas and the importance of skilled care should be emphasized. Women should be encouraged to utilize antenatal and delivery services.